2018
DOI: 10.1021/acsami.8b12363
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Wearable Pressure Sensors Assembled by Surface-Patterned Polyolefin Elastomer Nanofiber Membrane Interpenetrated with Silver Nanowires

Abstract: Wearable pressure sensors with ultrahigh sensitivity and flexibility have garnered tremendous attention because of their abilities to mimic the human somatosensory system and perceive surrounding pressure distribution. Herein, an ultrasensitive pressure sensor was fabricated with surface-patterned nanofibrous membranes (SPNMs) via a facile replica method from available plain-weaved nylon textiles. The SPNMs were composed of internal threedimensional interpenetrating polyolefin elastomer nanofibers and silver n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 39 publications
(47 reference statements)
0
43
0
Order By: Relevance
“…According to the definition of equation of sensitivity (Equations (1) and (2)) [8,9] the Δ R/R 0 curve can be divided into two linear sections and fitted. The slope of the two linear fitted line can be considered as the sensitivity in that pressure range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the definition of equation of sensitivity (Equations (1) and (2)) [8,9] the Δ R/R 0 curve can be divided into two linear sections and fitted. The slope of the two linear fitted line can be considered as the sensitivity in that pressure range.…”
Section: Resultsmentioning
confidence: 99%
“…With the rapid development of the information technology, flexible pressure sensors have been extremely concerned due to their potential in human machine interface, flexible robots, wearing electronic equipment, and flexible electronic skin [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15]. Normally, flexible pressure sensors are divided into three types: capacitive, piezoelectric, and piezo-resistive.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is much less expensive than photolithography techniques, nevertheless it does not allow for design changes in the micro-structuring due to limitations regarding the objects available to act as molds. Several objects have been used as molds, from sandpaper [ 130 , 166 , 167 , 168 , 169 , 170 , 171 ] to paper [ 39 ], leaves of several plants’ species [ 38 , 43 , 142 , 172 , 173 , 174 , 175 , 176 , 177 ], insect wings [ 142 ], animals skin [ 178 ], and fabrics [ 140 , 179 , 180 , 181 , 182 ]. PDMS is once again the most chosen material for the micro-structured films [ 38 , 39 , 130 , 140 , 142 , 167 , 168 , 169 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 182 ], as well as PDMS-based composites with graphite [ 166 , 170 ] or carbon nanotubes (CNTs) [ 181 ].…”
Section: Pressure Sensorsmentioning
confidence: 99%
“…When a pressure is applied, the two films contact, and a significant current is generated. For instance, Wei et al demonstrated a wearable pressure sensor with the structure of two conductive AgNWs-coated cotton sheets [29]. Zhou et al designed a pressure sensor with a printed textile electrode and AgNW-coated cotton fabric [30].…”
Section: Introductionmentioning
confidence: 99%